The Present Situation of the Fisheries Sector in Iraq: A Critical Review - Harlıoğ, Muzaffer Mustafa; Mustafa, Shokri; Batool, Zahra (My University, 2023)
In this review, the status of fisheries in Iraq is described. Iraq has two main water resources, the Tigris and Euphrates Rivers, forming a water area of approximately 700,000 hectares. Surface waters are distributed as natural lakes (39%), dam lakes (13.3%), and rivers and their tributaries (3.7%). On the other hand, marshes constitute 44% of the water sources in Iraq. The Iraqi government began recording fish production from wild and aquaculture in 1986. Total fish production from freshwaters in Iraq in 1991 and 1998 were 18,800 and 30,000 tons, respectively. In 2020, the total fish production in Iraq reached to 241,848 tons (Anonymous, 2022a). The bulk of fish production belonged to carps followed by barbs (genus Barbus) and trouts. With respect to capture fishing in Iraq, a variety of trawl nets (single-bag and multi-bag) and gillnets have commonly been used. The 1970s and 1980s were characterized by low consumption of fish meat (i.e., 4.3 kg in 1979), but it has gradually increased over the last years and has reached a remarkable 10 kg per capita in 2020. In this review, freshwater and marine fish species, aquaculture production and wild catch, institutions and centers specialized in researching and developing fisheries, fish meat consumption, problems of the fishing industry and potential solutions to develop the fishing industry in Iraq are outlined. This is the first study on the present status of fisheries in Iraq.
Keywords: Barbus; Aquaculture; carp; trout; fish production; fish consumption; marine fish